Ukraine : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This paper describes economic developments in Ukraine during the 1990s. In 1996, Ukraine achieved a measure of macroeconomic stability for the first time since gaining independence. Inflation, which at times had bordered on hyperinflation, fell to an average monthly rate of 2.8 percent and, except in months with major administered price changes, remained low throughout the year. This trend continued in 1997, when inflation averaged less than 1 percent a month during the first half of the year.